2012
DOI: 10.2209/tdcpublication.53.45
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Roughness of Titanium Dental Implant Placed under Periosteum on Gene Expression of Bone Morphogenic Markers in Rat

Abstract: Various bone matrix proteins are produced during the process of osteogenesis. Many previous studies suggested that the topography of an implant surface might affect the expression of osteoblast-mediated cytokines. However, these earlier studies were performed using in vitro cell culture. This study investigated the influence of the surface topography of a titanium implant placed under the periosteum on the gene expression of bone morphogenic markers in rat. Six custom-made implants with a rough upper surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…Micro-rough surface implants have been shown to increase osteoblastic cell attachment and differentiation [54][55][56][57][58] and result in higher osteogenic gene expression (ALP, bone sialoprotein, OC) compared with machined implants [59,60]. Our study also found a significant increase in the expression of osteoblast markers (ALP and OC) in the SHAM micro-rough implant group, which is consistent with previously reported data [59] and provides further evidence that micro-rough surfaces have an enhanced osteogenic capacity compared to machined surfaces. However, the micro-rough implants in the OVX group did not show an increase in osteogenic gene expression despite an increase in the number and organization of osteoblasts shown histologically (compared to the OVX machined group).…”
Section: Discussionmentioning
confidence: 99%
“…Micro-rough surface implants have been shown to increase osteoblastic cell attachment and differentiation [54][55][56][57][58] and result in higher osteogenic gene expression (ALP, bone sialoprotein, OC) compared with machined implants [59,60]. Our study also found a significant increase in the expression of osteoblast markers (ALP and OC) in the SHAM micro-rough implant group, which is consistent with previously reported data [59] and provides further evidence that micro-rough surfaces have an enhanced osteogenic capacity compared to machined surfaces. However, the micro-rough implants in the OVX group did not show an increase in osteogenic gene expression despite an increase in the number and organization of osteoblasts shown histologically (compared to the OVX machined group).…”
Section: Discussionmentioning
confidence: 99%
“…The surface properties, including surface roughness, free energy and tomography, play a key factor for cellular adhesion and proliferation [ 6 , 35 - 39 ]. In this study, surface modification by OP provided better condition of cell spreading and growth, especially after 5 min OPT.…”
Section: Discussionmentioning
confidence: 99%
“…According toT. Haraet al research results 6 , rough surface implants under the periosteum contribute to the expression of alkaline phosphatase, bone sialoprotein and osteocalcin. The influence of chitosan-collagen composites that could induce invivo-formation of new bone tissue around the surface of the titanium implant was also studied.…”
Section: Introductionmentioning
confidence: 99%